Exuberant ingrown nail: Satisfactory esthetics results combining surgery techniques - Edgar Ollague Cordova; Kleber Ollague Cordova; Ana Cecilia Studart; Andreia Leverone; Paula Regazzi; Danielle Quintella (Wolters Kluwer Medknow Publications, 2018)
Subcutaneous onychocryptosis is one of the most common diseases of the nail unit. It causes significant morbidity and disability in daily life and may become chronic if not treated. It is classified in three stages as defined by Heifetz and Frost. Conservative treatment is favored in mild cases, while surgery is necessary for stages 2 and 3 ingrown toenails. We describe a case of subcutaneous onychocryptosis Grade III, in which alpha stitch and Howard-Dubois techniques improved final esthetic result. The aim of this article is to present an exuberant case of onychocryptosis and how a combination of surgical techniques can produce a better outcome.